Reinforcing Character Education Values on Islamic Education in the Time of Distance Learning - Sopiah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study aims to describe the results of the critical analysis regarding some strategies that can be adopted in building character education values in Islamic education, especially in the time of distance learning. These strategies are deemed to be crucial parameters in the learning process so that the learning process will not merely on cognitive achievement. Grounded in library research, study findings promote four strategies to be employed in building character education values in Islamic education in the age of distance learning. First, teacher-parent communication was optimized via online media, e.g. social media, digital mutaba’ah books (communication book: a teacher-parent daily communication book) based on Google form applications, or offline media, e.g. printed Mutaba’ah books. Second, the character education value-based learning module was designed to highlight several materials related to character education in the form of motivational videos, inspirational stories, and so forth. Third, various innovative learning methods, including problem-solving, positive habituation, and reflection methods were undertaken to emphasize the affective and psychomotor indicators. Forth, a comprehensive learning evaluation was developed to leverage not only cognitive skills but also the affective and psychomotor domains.